2011
DOI: 10.1371/journal.pone.0022401
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Comparison of Innate Responses to Viral and Bacterial Pathogens in Mouse and Macaque

Abstract: Viral and bacterial infections of the lower respiratory tract are major causes of morbidity and mortality worldwide. Alveolar macrophages line the alveolar spaces and are the first cells of the immune system to respond to invading pathogens. To determine the similarities and differences between the responses of mice and macaques to invading pathogens we profiled alveolar macrophages from these species following infection with two viral (PR8 and Fuj/02 influenza A) and two bacterial (Mycobacterium tuberculosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…DREM has proven to be successful at modeling several biological processes and systems in multiple organisms, including stress response in yeast and E. coli (Ernst et al, 2007(Ernst et al, , 2008, human and mouse development (Schulz et al, 2013;Roy et al, 2010;Mendoza-Parra et al, 2011), and immune and disease progression Zinman et al, 2011;Laurenti et al, 2013).…”
Section: Dynamic Regulatory Events Miner (Drem)mentioning
confidence: 99%
“…DREM has proven to be successful at modeling several biological processes and systems in multiple organisms, including stress response in yeast and E. coli (Ernst et al, 2007(Ernst et al, , 2008, human and mouse development (Schulz et al, 2013;Roy et al, 2010;Mendoza-Parra et al, 2011), and immune and disease progression Zinman et al, 2011;Laurenti et al, 2013).…”
Section: Dynamic Regulatory Events Miner (Drem)mentioning
confidence: 99%
“…Several genomic and proteomic studies have also been carried out in influenza-infected macaques [1,42]. In a recent study, Andrea L. Kroeker carried out the differential expression of host protein in primary human bronchial airway epithelial (HBAE) cells and she reported that the down regulated proteins generally belong to cell adhesion and lipid metabolism and up regulated proteins were from the host defense responses against influenza infection [44]. Most proteomic studies investigating the effect of influenza infection have been carried out in different cell lines and primary macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…As evidenced above, many viral infections associated with neutrophil infiltration have RNA genomes. Host cells detect RNA viruses primarily through RLR as well as TLR, whereas bacteria rely on a different group of PRRs to detect extracellular PAMPs (327,328,357,505). Because of the importance in diagnostics, many studies have focused on biomarkers that identify bacterial versus viral infection (e.g., (506,507)).…”
Section: Host Response To Viral Versus Bacterial Infection Specific mentioning
confidence: 99%
“…In short a single reliable biomarker of bacterial versus viral infection has yet to be found. In a recent study, it was among a group of early conserved differentially expressed genes across species (mouse and macaque) and pathogens (IAV and bacterial), all of which were the direct result of an upregulation of ISGs (505). For example, IFNb, IL-1a, IL-6, IL-23a, TIMP1, M-CSF, ISG15, CCL2, CCL5, CXCL10, and CD40 were all common to the early host immune response to lung infection (505).…”
Section: Host Response To Viral Versus Bacterial Infection Specific mentioning
confidence: 99%
See 1 more Smart Citation